Leaf removal timing and its influence on wine grape performance ‘Sauvignon Blanc’ in high altitude region - Würz, Douglas André; Allebrandt, Ricardo; Marcon Filho, José Luiz; Bem, Betina Pereira de; Brighenti, Alberto Fontanella; Rufato, Leo; Kretzschmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2018)
The winegrape is characterized as a demanding species in cultural dealings and in order to reach optimal conditions at the time of harvest it is fundamental that the management techniques are adequate the characteristics of each region, being the leaf removal has been an important management of the vegetative canopy, which can improve the chemical composition of the bunches and increase the productive efficiency of the vine. The objective of this study was to evaluate the leaf removal effect on the agronomic performance and maturation ad the productive efficiency of the Sauvignon Blanc grape in high altitude regions of Santa Catarina. The experiment was conducted in 2015 and 2016 vintages, in a commercial vineyard, located in São Joaquim, Santa Catarina State (28°17’39”S; 49°55’56”W, altitude 1,230m a.s.l.). The leaf removal was carried out in cluster zone in the following phenological stages: full bloom, buckshot berries, pea-sized berries, veraison, 15 days after veraison and control without leaf removal. The results were submitted to analysis of variance and Scott-Knott test (5% probability). It was observed that the leaf removal carried before veraison increase the fertility index. The leaf removal carried out in the phenological pea-sized berries and veraison presented the highest yields in relation to the other phenological stages and plants not submitted to the management of leaf removal. In addition, the leaf removal improved the technological and phenolic maturation of the Sauvignon Blanc grape when it was carried out in the phenological stages buckshot berries and pea-sized berries in the two harvests evaluated. The results of this study evidenced the importance the leaf removal to obtain a must with potential for the elaboration of quality fine wines, especially when carried out between the phenological stages of buckshot berries and pea-sized berries. Therefore, the leaf removal of the Sauvignon Blanc grapevine in high altitude regions should be considered an indispensable management practice for the vitivinicultor.